Managing fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), with Bt maize and insecticides in southern Brazil. Issue 12 (12th September 2017) - Burtet, Leonardo M; Bernardi, Oderlei; Melo, Adriano A; Pes, Maiquel P; Strahl, Thiago T; Guedes, Jerson VC
Abstract: BACKGROUND: Maize plants expressing insecticidal proteins of Bacillus thuringiensis are valuable options for managing fall armyworm (FAW), Spodoptera frugiperda, in Brazil. However, control failures were reported, and therefore insecticides have been used to control this species. Based on these, we evaluated the use of Bt maize and its integration with insecticides against FAW in southern Brazil. RESULTS: Early‐planted Agrisure TL, Herculex, Optimum Intrasect and non‐Bt maize plants were severely damaged by FAW and required up to three insecticidal sprays. In contrast, YieldGard VT Pro, YieldGard VT Pro 3, PowerCore, Agrisure Viptera and Agrisure Viptera 3 showed little damage and did not require insecticides. Late‐planted Bt maize plants showed significant damage by FAW and required up to four sprays, with the exceptions of Agrisure Viptera and Agrisure Viptera 3. Exalt (first and second sprays); Lannate + Premio (first spray) and Avatar (second spray); and Karate + Match (first spray) and Ampligo (second spray) were the most effective insecticides against FAW larvae in Bt and non‐Bt maize. CONCLUSION: Maize plants expressing Cry proteins exhibited FAW control failures in southern Brazil, necessitating insecticidal sprays. In contrast, Bt maize containing the Vip3Aa20 protein remained effective against FAW. However, regardless of the insecticide used against FAW surviving on Bt maize, grain yields were similar. © 2017 Society of Chemical Industry